On Abolishing Symmetry Requirements in the Formulation of a Five-Level Selective Harmonic Elimination Pulse-Width Modulation Technique - Dahidah, Mohamed. S. A.; Agelidis, Vassilios G.; Rao, Machavaram V. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2006)
Selective harmonic elimination pulse width modulation (SHE-PWM) techniques offer a tight control of the harmonic spectrum of a given voltage waveform generated by a power electronic converter along with a low number of switching transitions. These optimal switching transitions can be calculated through Fourier theory, and for a number of years quarter-wave and half-wave symmetries have been assumed when formulating the problem. It was shown recently that symmetry requirements can be relaxed as a constraint. This changes the way the problem is formulated, and different solutions can be found without a compromise. This letter reports solutions to the switching transitions of a five-level SHE-PWM when both the quarter- and half-wave symmetry are abolished. Only the region of high-modulation indices is reported since the low-modulation indices region requires a unipolar waveform to be realized. Selected simulation and experimental results are reported to show the effectiveness of the proposed method.